Aging and Terrorism - Mustafa, Sheraz; Mehfooz, Kamran (Pakistan Journal of Humanities and Social Sciences, 2025)
This paper examines how aging affects terrorism following Ehrlich and Liu (2002). The central theme of this paper is to analyse the tendency of aging societies to resort to the incidents of terrorism. With a relative increase of aged population, the unemployment may fall given the lesser pressure in labour market and consequently, the inclination of youth to resort to terrorism declines. International panel data is composed of 89 countries from 1990-2022 is collected and the negative binomial regression model is applied to confirm the argument proposed in this paper. Furthermore, a rise in the size of the aged population in either democracies or countries with higher income levels is found to discourage terrorism.